New remains of Lophiaspis maurettei (Mammalia, Perissodactyla) from the early Eocene of France and the implications for the origin of the Lophiodontidae. Issue 6 (10th December 2020) - Vautrin, Quentin; Tabuce, Rodolphe; Lihoreau, Fabrice; Bronnert, Constance; Gheerbrant, Emmanuel; Godinot, Marc; Metais, Gregoire; Yans, Johan; Dutour, Yves; Vialle, Nicolas; Philip, Jean; Billet, Guillaume
ABSTRACT: The Lophiodontidae are endemic perissodactyls from Europe that flourished during the Eocene. Despite their preponderance in the European fossil record, their exact origin and relationships within the perissodactyls remain unknown due to the rare and fragmentary material in the early Ypresian, the time of their earliest radiation. Lophiaspis maurettei is the oldest and earliest diverging lophiodontid known to date but is unfortunately poorly known. We describe here the results of new excavations of the type locality of Palette. Important new material including complete skulls, mandibles, post-cranial elements and juvenile specimens lead us to revise Lophiaspis maurettei from Palette and other localities and to describe novel morphology for this species. According to an original phylogenetic analysis, based on a revised matrix of dental, cranio-mandibular and postcranial characters, Ls. maurettei is an early diverging lophiodontid morphologically close to Protomoropus and Paleomoropus, two basal chalicotheres, known from Asia and North America, respectively. Our resulting topology does not support the previously proposed inclusion of the lophiodontids within the Ceratomorpha and supports a position within the suborder Ancylopoda, close to some Eomoropidae representatives. These results imply that Ls. maurettei was restricted to Southern Europe during the early Eocene, which would be compatible with an Asian origin for lophiodontids in accordance with the evolutionary history of other perissodactyls and placental mammals.